2013
DOI: 10.1590/sajs.2013/1200
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes to science in South Africa

Abstract: In a global environment characterised by the growing role of science and technology in our economic, social, and political lives, an international research agenda has arisen to measure and understand how science and technology are perceived and evaluated by the public. In 2010, the South African Social Attitudes Survey included 20 items to measure public attitudes towards science, knowledge about science, and sources of information about science. This household survey was administered to a representative, stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 14 publications
0
37
2
Order By: Relevance
“…An analysis of the items which measured scepticism towards science showed that the South African population seems to have become more cautious about the level of trust they place in science, and more concerned about the impacts of science. 8,9 The survey also asked questions related to the attitudes of respondents towards science as a subject at school. The results showed that 41% of South Africans felt that the science learned at school was not useful in their daily lives, while almost a third (30%) did not see its value in their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the items which measured scepticism towards science showed that the South African population seems to have become more cautious about the level of trust they place in science, and more concerned about the impacts of science. 8,9 The survey also asked questions related to the attitudes of respondents towards science as a subject at school. The results showed that 41% of South Africans felt that the science learned at school was not useful in their daily lives, while almost a third (30%) did not see its value in their jobs.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these attitudes affect outcomes such as support for public funding among the voting population. 1 For South Africa, certain initial findings have led researchers to conclude that this country has a unique fingerprint with regard to public attitudes towards S&T. 4 South Africans generally show a mix of positive and negative attitudes about S&T. In this paper, 'promises' refer to people's positive expectations and beliefs about the benefits of S&T, whereas 'reservations' refer to negative views about S&T. A comparison of recent data with earlier data 5 showed that for South Africans, scientific promises have dropped slightly whereas some reservations have increased significantly. Age and education seem to influence the promise−reservation ratio in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 While the public communication of science, including the factors that influence scientists in terms of their communication with lay audiences, has attracted considerable research interest over the last few decades, local studies were mostly limited to explorations of public science literacy and attitudes to science. 32 Only two studies investigated interactions between South African scientists and journalists 33,34 and both highlighted gaps in understanding and skills deficits on the sides of both journalists and scientists.…”
Section: The South African Context For Public Science Communicationmentioning
confidence: 99%